Early 2D/3D ultrasound diagnosis of pleural effusion in fetuses with Turner syndrome. Issue 9 (19th September 2018) - Kosinski, Przemyslaw; Ismail, Mahmoud; Abramowicz, Jacques S.
Abstract: Most guidelines on ultrasound examinations during pregnancy do not recommend routine early pregnancy scan in uncomplicated and asymptomatic pregnancies (ie, before 10 weeks based on last menstrual period). There is, however, a growing patient's expectation to have an early scan to confirm dating and verify the pregnancy is intrauterine and viable. We present three well‐documented cases of patients who had an early (7‐8 weeks) dating transvaginal scan revealing pleural effusion in the embryo. In all cases cytogenetic analysis confirmed monosomy for the X chromosome, consistent with a clinical diagnosis of Turner syndrome.